Influence of riser design on macrosegregation in static castings. (February 2015) - Zhang, S. L.; Johnson, D. R.; Krane, M. J. M.
<x content-type="archive" xml:space="preserve">Abstract</x> The flow between a casting and riser and the consequent macrosegregation development in an aluminium alloy is examined. The riser is designed using Campbell's rules and solidification is simulated. The influence of cooling conditions and riser shape on macrosegregation patterns is studied. The relative importance of buoyancy and shrinkage induced flows is also simulated. For castings with a fixed riser shape, the average composition in the cast part increases due to the exchange of interdendritic fluid between the riser and the part. This exchange is smaller at higher solidification rates and when the bottom of the mould is chilled. Although the buoyancy induced flow does move some interdendritic liquid from the riser to the casting, shrinkage is more significant in increasing its average composition. A wider riser provides a barrier to flow, slowing the introduction of heavier interdendritic liquid from the riser into the casting, keeping it closer to the nominal composition.